2021
DOI: 10.3389/frsc.2021.638278
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Mobile Health Tools to Support COVID-19 Training and Surveillance in Ogun State Nigeria

Abstract: Mobile health (mhealth) tools delivered through wireless technology are emerging as effective strategies for delivering quality training, ensuring rapid clinical decision making, and monitoring implementation of simple and effective interventions in under-resourced settings. We share our early experience of developing and deploying the InStrat COVID-19 health worker training application (App) in Ogun State, Western Nigeria where the country's first COVID-19 case was reported. This App was designed to directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Insight from the stories of MSC suggests that implementing multiple digital health interventions for 2 years within a supportive policy environment in Ondo State had generated significant interest in government and from other stakeholders in the health sector to adopt eHealth innovations. An example of increased adoption of eHealth innovations by the Ondo State Government is the launch in December 2019, of a new electronic Contributory Health Insurance Scheme (eCHIS) as a pathway to promoting equitable access to essential healthcare services and accelerating universal health coverage ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Insight from the stories of MSC suggests that implementing multiple digital health interventions for 2 years within a supportive policy environment in Ondo State had generated significant interest in government and from other stakeholders in the health sector to adopt eHealth innovations. An example of increased adoption of eHealth innovations by the Ondo State Government is the launch in December 2019, of a new electronic Contributory Health Insurance Scheme (eCHIS) as a pathway to promoting equitable access to essential healthcare services and accelerating universal health coverage ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Details of the deployment of this app have been reported previously. 15 The app allowed for (1) training of health workers on COVID-19; (2) provision of users with desk guides to rapidly screen, identify and manage suspected COVID-19 cases. 16 This app was subsequently deployed at scale to 25 states of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the deployment of this app have been reported previously. 15 The app allowed for ( 1) training of health workers on COVID-19;…”
Section: Introductionmentioning
confidence: 99%
“…Regarding private-public partnerships ( 34 ), analysis revealed that this eHealth project was a promising example of public-private partnerships (PPP) between local technology companies and the governments in Nigeria for designing and delivering digital health initiatives for public benefit. The PPP approach provided a viable chance of success for sharing resources, capabilities and project risks.…”
Section: Resultsmentioning
confidence: 99%
“…In a public-private partnership with InStrat, the Ondo State Government has (in December 2019) adopted a package of inter-related digital health innovations (including digitization of health data and an electronic health insurance platform) to facilitate equitable access to essential healthcare services as a pathway to achieving universal health coverage. This new project, currently implemented in nine general hospitals in the Ondo State, is being incrementally expanded to 203 PHC facilities in the state; (ii) partnership between InStrat and the multiple State Governments using an adaptation of the VTR Application to develop a COVID-19 training App to provide FHWs with accurate and up-to-date information about COVID-19 to enable them to quickly identify, screen and manage COVID-19 suspects across multiple states in Nigeria ( 34 ).…”
Section: Resultsmentioning
confidence: 99%